Synergistic photocatalytic effect between green LED light and Fe3O4/ZnO-modified natural pumice: A novel cleaner product for degradation of methylene blue. (October 2020) - Taheri-Ledari, Reza; Valadi, Kobra; Gharibi, Saideh; Maleki, Ali
Graphical abstract: Highlights: A novel nature-based photocatalytic system is presented. Synergistic catalytic effect between green light and a nanocatalyst has been studied. Precise analytical method is presented for obtaining the photocatalytic efficiency. High degradation yield has been observed for methylene blue dye. Abstract: Herein, an efficient photocatalytic system is prepared and applied for photocatalytic degradation of methylene blue (MB), under green light irradiation. This catalytic system is made of the nanosized ingredients including iron oxide nanoparticles (Fe3 O4 NPs) and zinc oxide nano-rods (ZnO NRs), to provide a wide surface active area. The first and foremost point from the structural aspect is the magnetic property enhancement through well composition of the natural pumice micro-plates with Fe3 O4 NPs, as two magnetic ingredients. Through this property, the catalyst's particles are conveniently collected and reused for additional eight times. Concisely, the highest photocatalytic efficiency (85.5%) has been obtained through using 50?mg of ZnO/Fe3 O4 @pumice photocatalyst under green LED light (7?W, 526?nm) irradiation, for 60?min. In this study, a plausible photocatalytic mechanism for degradation of the MB by the produced photocatalytic system is suggested as well.